A multi-responsive supramolecular heparin-based biohybrid metallogel constructed by controlled self-assembly based on metal–ligand, host–guest and electrostatic interactions. Issue 17 (7th July 2021) - Wu, Gui-Yuan; Liang, Chao; Li, Hao; Zhang, Xianyi; Yao, Guanxin; Zhu, Fan-Fan; Hu, Yi-Xiong; Yin, Guang-Qiang; Zheng, Wei; Lu, Zhou
Abstract : A new family of supramolecular heparin-based biohybrid metallogels with multiple stimuli-responsive behaviours was constructed through the controlled self-assembly based on three orthogonal interactions within a single system. Abstract : Heparin-based gels constructed by non-covalent interactions can self-assemble into various nanostructures in solution, and can find applications in many fields such as nanodevices, drug delivery, and stimulus responsive materials synthesis. Herein, we describe the construction of a new class of supramolecular heparin-based biohybrid metallogels (HBMGs) with multiple stimuli-responsive behaviours through controlled self-assembly based on three orthogonal interactions, namely metal–ligand, host–guest and electrostatic interactions, within a single system. Specifically, a tris-[2]pseudorotaxane hexagonal metallacycle was synthesized by the orthogonal coordination-driven self-assembly and host–guest interactions. It was found that the obtained positively charged tris-[2]pseudorotaxane metallacycle can further form supramolecular HBMGs with heparin, one of the highest negatively charged biomolecule, via acid–base controlled multiple electrostatic interactions at lower concentrations. Notably, thermo-, acid–base and cation-induced gel–sol transitions were found to be completely reversible, reflecting the dynamic and controllable nature of such supramolecular materials. Hence, this research not only provides a simple yet highly efficient strategy for the fabrication of functional biohybrid materials involving metal–organic complexes and biomacromolecules, but also offers broad prospects for supramolecular engineering using precisely controlled self-assembly strategies.